Populism and Democracy: Analysis on the Phenomenon of Populism in Indonesia and the Crisis of Democracy - Jhon Mai, Adrianus; Jemadin, Silfanus; Erwin, Salfianus; Rifandi Somi4, Marthen (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2024)
This article first discusses the phenomenon of populism in Indonesia which has the potential to pose a threat to the democratic system in Indonesia. Of course, this article was written as a response to the populist movement which has recently been hotly discussed because populism is growing rapidly in the social and political system in Indonesia. The intention of this article is to provide advice to the Indonesian people, to understand the phenomenon of populism which has transformed into a political weapon and maneuver by political actors, for the benefit of their political groups or parties. This article will use literature study to collect data and information to lead to a discussion and conclusion. The aim of this article is to examine the phenomenon of populism in Indonesia which has the potential to become a serious threat to the democratic system. Then to provide education to the Indonesian people regarding the populist movement which uses all kinds of methods or certain instruments to perpetuate their power as political actors.